Revolutionizing immunization: a comprehensive review of mRNA vaccine technology and applications - Kai Yuan Leong; Seng Kong Tham; Chit Laa Poh (Virology Journal)
Abstract Messenger RNA (mRNA) vaccines have emerged as a transformative platform in modern vaccinology. mRNA vaccine is a powerful alternative to traditional vaccines due to their high potency, safety, and efficacy, coupled with the ability for rapid clinical development, scalability and cost-effectiveness in manufacturing. Initially conceptualized in the 1970s, the first study about the effectiveness of a mRNA vaccine against influenza was conducted in 1993. Since then, the development of mRNA vaccines has rapidly gained significance, especially in combating the COVID-19 pandemic. Their unprecedented success during the COVID-19 pandemic, as demonstrated by the Pfizer-BioNTech and Moderna vaccines, highlighted their transformative potential. This review provides a comprehensive analysis of the mRNA vaccine technology, detailing the structure of the mRNA vaccine and its mechanism of action in inducing immunity. Advancements in nanotechnology, particularly lipid nanoparticles (LNPs) as delivery vehicles, have revolutionized the field. The manufacturing processes, including upstream production, downstream purification, and formulation are also reviewed. The clinical progress of mRNA vaccines targeting viruses causing infectious diseases is discussed, emphasizing their versatility and therapeutic potential. Despite their success, the mRNA vaccine platform faces several challenges, including improved stability to reduce dependence on cold chain logistics in transport, enhanced delivery mechanisms to target specific tissues or cells, and addressing the risk of rare adverse events. High costs associated with encapsulation in LNPs and the potential for unequal global access further complicate their widespread adoption. As the world continues to confront emerging viral threats, overcoming these challenges will be essential to fully harness the potential of mRNA vaccines. It is anticipated that mRNA vaccines will play a major role in defining and shaping the future of global health.